Genetic differentiation within Vetiveria zizanioides: selection and breeding of commercial perfumery grass Vetiver. Issue 4 (2nd October 2018) - Dhawan, Sunita Singh; Gupta, Pankhuri; Mishra, Anand; Singh, Susheel Kumar; Chauhan, Harmesh Singh
ABSTRACT: Eighteen Vetiveria zizanioides accessions were analyzed for genetic diversity by Random Amplified Polymorphic DNA (RAPD) including CIM-Vridhi, an elite released variety. Twenty MAP primers were used to detect the DNA polymorphism and a total of 152 bands were obtained, out of which 45 were monomorphic, 137 polymorphic, 15 unique bands and 73.1% polymorphism were estimated. The average polymorphic information content (PIC) value obtained with RAPD markers was 0.44; marker index (MI), effective multiplex ratio (EMR), and resolving power (RP) were 2.39, 5.09, and 22.3, respectively. Principal component analysis (PCA) derived for RAPD markers illustrated the first three principal coordinate components accounted for 76.75% of the genetic similarity variance.